Vulnerability and access to land in the commune of Diama - Moussa Sarr (African Journal on Land Policy and Geospatial Sciences, 2023)
The issue of equal access of citizens to land remains a concern of public authorities to respond to issues related to household food security, especially in rural areas. Along the way, a legal and regulatory framework has been developed to give substance to the development options of the primary sector consisting of agriculture and livestock. However, the criteria identified in the context of the allocation of land in the national domain are sometimes biased due to considerations based on the social position of the person concerned. Indeed, the notion of capacity to be able to develop the land requested naturally excludes certain strata that do not meet the financial conditions required for such exploitation. According to our surveys, the category of people who find themselves in this situation is often made up of women, young people, the elderly and those with disabilities. However, there are a series of measures that would aim to restore the equality of citizens for the access and use of natural and land resources. Land projects and programs in collaboration with the State and rural communes make consideration of the gender aspect a component. This concern has enabled vulnerable groups to be better taken into account in the land allocation activities of the national domain at the level of the commune of Diama, notwithstanding the breakthrough of large-scale land acquisitions (ATE).